Analisis Pengaruh Memutuskan Menjadi Nasabah Bank Syariah Sragen dengan Kepercayaan Sebagai Variabel Intervening - Ika Yulianti (Institut Agama Islam Negeri Parepare, 2021)
This study aims to analyze what factors are able to influence the customer's decision to choose Syaiah Bank Sragen with the variables of consumer knowledge, halal lifestyle, and bank reputation on the decision to become a Sragen sharia bank customer with trust as an intervention variable. In this research, quantitative method. The data used is primary data, through the distribution of questionnaires to the respondents, namely the customers of Sharia Bank Sragen as many as 100 respondents. This hypothesis is a multiple linear regression analysis research with t test, f test and deter coefficient test (Adjuster R2) which is processed with SPSS version 24 program. The results of this study state that halal lifestyle and bank reputation have a positive and significant impact on the decision to become a customer of Bank Sragen Syariah. . Meanwhile, consumer knowledge has no effect on the decision to become a customer. Trust has a positive and significant effect on the decision to become a customer. And consumer knowledge and reputation also have a positive and significant impact on trust. And trust is able to mediate consumer knowledge and bank reputation on the decision to become a custome